Poster 265: ACL Reconstruction in Skeletally Immature Patients: Do ACL Graft Tear and Complication Rates Differ Based on Surgical Technique? A Systematic Review. Issue 7 (30th July 2022) - Coene, Ryan; Pang, Joshua; Fabricant, Peter; Nepple, Jeffrey; Matava, Matthew; Heyworth, Benton
Objectives: Despite a notable increase in studies investigating outcomes following ACL reconstruction (ACLR) in pediatric patients in the last decade, there remains a dearth of comparative studies designed to elucidate the optimal technique(s) for this active, high-risk sub-population. The obejctive of the current study was to compare the rates of ACL graft tear, complications, and return-to-sport (RTS) between categories of ACLR techniques in skeletally immature patients. Our hypothesis was that complication rates would be similar between techniques, while ACL graft tear rates would be greater in transphyseal (adolescent) ACLR than physeal-sparing (pediatric) ACLR. Methods: A literature search indexed from the earliest available date to January 5, 2021 was performed using the PubMed/MEDLINE, Embase, and Cochrane databases for relevant journal articles with standard inclusion/exclusion criteria utilized for systematic reviews. Further exclusions were studies of ACL repair, revision ACLR, ACLR with allograft or bone-patellar tendon-bone (BTB) autograft. Cohorts of adolescent patients undergoing transphyseal ACLR were distinguished from those of pediatric patients undergoing physeal-sparing techniques, which were further sub-classified as all-epiphyseal (AE), iliotibial band (ITB)/modified Macintosh, and partial transphyseal (PTP). Transphyseal ACLR was further classified based on graft type (hamstring vs. quadriceps autograft). Primary outcomes included reoperation for ACL graft tear, non-ACL/meniscus complications, and RTS rates. Meta-analysis for each outcome incidence rate was conducted within each subgroup, and overall, using a random effects generalized linear mixed model with logit link. Results: 44 studies published between 2001 and 2021 from 15 different peer-reviewed journals were included. The total number of patients within each subgroup were as follows: Transphyseal, 2, 130 patients; AE, 232 patients; ITB, 274 patients; PTP, 99 patients. The mean age of the adolescent/transphyseal group was 13.4 years (range, 11.0-14.8), compared to 12.3 years (range, 11.0-14.8) in the pediatric/physeal-sparing group (AE, 12.6 years; ITB, 11.5 years; PTP, 12.6 years). Mean duration of follow-up was reported in 93.2% of the studies and was 4.0 years (range, 1.6-10.6 years). ACL graft tear, contralateral ACL tear, complications, and RTS were not significantly different between transphyseal and physeal-sparing techniques (all p>0.05) (Table 1). ITB reconstruction was not associated with any significant differences in ACL graft tear or RTS rates compared to other physeal-sparing techniques, but did demonstrate a significantly lower complication rate (ITB, 2.9%; AE, 10.8%; PTP, 15.3%; p=0.005). The most reported non-ACL/meniscus complications were arthrofibrosis (n=35) and growth disturbance (including angular deformity and leg length discrepancy, n=23). Conclusions: Unlike the findings of smaller, single-center clinical series, we found no differences in the clinical results of younger pediatric patients undergoing physeal-sparing ACLR and relatively older, skeletally immature adolescents undergoing transphyseal ACLR when the pediatric ACLR literature was analyzed in a pooled fashion. Amongst physeal-sparing techniques, the ITB/modified-MacIntosh ACLR demonstrated a significantly lower complication rate than all-epiphyseal and partial-transphyseal ACLR. Further prospective comparative research is required to directly compare ACLR techniques for differences in ACL graft tear rates. Table 1. Rates of ACL Graft Tear, complications, and Return to Sports in Skeletally Immature Sub-Populations